Synthesis of 6‐Aza‐2‐Hydroxyimino‐5‐Methylpyrimidine Nucleosides for Antiviral Evaluation. Issue 12 (8th December 2021) - Abou‐Elkhair, Reham A. I; Du, Jinxi; Wasfy, Abdalla A.; Khaill, Nisrin A.; Maaroof, Hend M.; Hassan, Marwa H.; Ahmed, Ayman S.; Hassan, Abdalla E. A.; Sheng, Jia
Abstract: The syntheses of a series of novel 6‐aza‐2‐hydroxyimino‐5‐methylpyrimidine and related nucleosides are described. A suitably protected 2‐methylthiopyrimidine nucleoside was selected as the precursor for installing a hydroxyimino moiety at the C‐2 position. The starting nucleobase 6‐aza‐5‐methyl‐2‐thiouracil is prepared in two steps from thiosemicarbazone and ethyl pyruvate. This is subjected to coupling with 1‐ O ‐acetyl‐2, 3, 5‐tri‐ O ‐benzoyl‐β‐D ‐ribofuranose under Vorbrüggen glycosylation conditions to provide the corresponding nucleoside in high yield. Activation of the nucleoside to the corresponding 2‐methylthio derivative followed by treatment with hydroxylamine hydrochloride in pyridine provides the corresponding 2‐hydroxyimino derivative in high yield. Finally, the synthesis of five free modified nucleoside analogs is described. The newly synthesized nucleosides have been evaluated against an RNA viral panel and moderate activity was observed against hepatitis C virus, Zika virus, and human respiratory syncytial virus. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of 6‐aza‐5‐methyl‐2‐thiouracil Basic Protocol 2 : Preparation of 6‐aza‐5‐methyl‐2‐thiouridine and 6‐aza‐5‐methyluridine Basic Protocol 3 : Preparation of 6‐aza‐2‐hydroxyimino‐5‐methyluridine Basic Protocol 4 : Preparation of 6‐aza‐2‐hydroxyimino‐5‐methyl‐4‐thiouridine and 6‐aza‐2‐hydroxyimino‐5‐methylcytosine